Pathways To Empowerment: A Grounded Theory Study Of Pakistani Female Doctoral Students In Malaysian Public Universities - Hyder, Shah Syed Faisal (2018)
In Pakistan, women have fewer opportunities for higher education than men. Additionally, a few women have a chance to avail foreign higher education. There are number of structural and socio-cultural barriers that impede women’s access to higher education. However, due to unprecedented importance of higher education, a few women strive and succeed to avail educational opportunities abroad where they also come across myriad challenges. To this end, the present study primarily aims to explore the challenges that Pakistani female students experience while pursuing their doctoral education in the selected universities of Malaysia.